Altered activity in the nucleus raphe magnus underlies cortical hyperexcitability and facilitates trigeminal nociception in a rat model of medication overuse headache - Prangtip Potewiratnanond; Supang Maneesri le Grand; Anan Srikiatkhachorn; Weera Supronsinchai (My University, 2019)
Abstract Background The pathogenesis of medication overuse headache (MOH) involves hyperexcitability of cortical and trigeminal neurons. Derangement of the brainstem modulating system, especially raphe nuclei may contribute to this hyperexcitability. The present study aimed to investigate the involvement of the nucleus raphe magnus (NRM) in the development of cortical and trigeminal hyperexcitability in a rat model of MOH. Results Chronic treatment with acetaminophen increased the frequency of cortical spreading depression (CSD) and the number of c-Fos-immunoreactive (Fos-IR) neurons in the trigeminal nucleus caudalis (TNC). In the control group, muscimol microinjected into the NRM increased significantly the frequency of CSD-evoked direct current shift and Fos-IR neurons in the TNC. This facilitating effect was not found in rats with chronic acetaminophen exposure. In a model of migraine induced by intravenous systemic infusion of nitroglycerin (NTG), rats with chronic exposure to acetaminophen exhibited significantly more frequent neuronal firing in the TNC and greater Fos-IR than those without the acetaminophen treatment. Muscimol microinjection increased neuronal firing in the TNC in control rats, but not in acetaminophen-treated rats. The number of Fos-IR cells in TNC was not changed significantly. Conclusion Chronic exposure to acetaminophen alters the function of the NRM contributing to cortical hyperexcitability and facilitating trigeminal nociception.
Keywords: Nucleus raphe magnus; Muscimol; Spinal trigeminal nucleus; Dorsal raphe nucleus; Raphe nuclei; Cortical Spreading Depression; Picrotoxin; Premovement neuronal activity; Raphe; Migraine and Headache Studies